Prognostic Significance of Immune-checkpoint Molecule PD-L1 in Classical Hodgkin Lymphoma: A Clinicopathologic Study of 120 Cases - Kubes, Vaclav; Kren, Leos; Sokol, Filip; Michalka, Jozef; Muzik, Jan; Arpas, Tomas; Krenova, Zdenka; Kral, Zdenek (In vivo (Athens, Greece), 2023)
BACKGROUND/AIM: Classic Hodgkin lymphoma (cHL) is a common B-cell malignancy. Despite the good prognosis, in some patients the standard chemotherapy and radiotherapy-based approach does not lead to long-term remission, and these patients eventually relapse. Moreover, the primary refractory disease is of major concern regarding prognosis. PATIENTS AND METHODS: We performed a retrospective analysis to evaluate PD-L1 expression in 120 patients with classic Hodgkin lymphoma (cHL). RESULTS: The median follow-up of the entire group of patients was 90 months. After initial therapy, complete remission was achieved in 113 (94.2%) patients. During the follow-up, cHL relapse/refractory disease was reported in 23 (19.2%) cases. A total of five patients died during the follow-up period, all from cHL progression. When determining PD-L1 expression on Hodgkin-Reed-Sternberg (HRS) cells, 37 cases (30.8%) were evaluated as negative, and 83 cases (69.2%) as positive. In the negative PD-L1 group of patients, no cHL relapse/refractory disease was observed during the follow-up period. However, out of 83 patients with positive PD-L1 expression on HRS cells, 23 (28%) showed relapse/refractory cHL. CONCLUSION: A significantly higher relapse rate was observed in PD-L1-positive patients diagnosed with cHL.
Keywords: Immune Checkpoint Proteins; proteiny kontrolních bodů imunitní reakce; overall survival; retrospektivní studie; lokální recidiva nádoru; B7-H1 Antigen; prognóza; Classic Hodgkin lymphoma; treatment; Hodgkin Disease; Neoplasm Recurrence, Local; lidé; Humans; antigeny CD274; Hodgkinova nemoc; Prognosis; Retrospective Studies; relapse; PD-L1 expression